MEMAKSIMALKAN DAYA TARIK ALAMIAH SEBAGAI STRATEGI PENGEMBANGAN WISATA ALAM GUNUNG PINANG SERANG BANTEN - Suliyanti, Suliyanti; Hasibuan, Ratna Sari; Cita, Ken Dara (Jurnal Nusa Sylva, 2021)
Gunung Pinang Nature Tourism is located in Kramatwatu District, Serang Regency. This nature tourism is managed by Perum Perhutani. This tour offers tourist attractions in the form of nature photos with the beauty background of Serang Regency.A variety of photo attractions are offered in this nature tourism. Affordable ticket prices make this natural tourism as one of nature tourism in Serang District. This research was conducted to determine the attraction of tourist attractions in Gunung Pinang natural Tourism, the method of study used is the assessment of ODTWA in the form of scoring or ranking on the potential of Gunung Pinang natural tourism based on guidelines according to Dirjen PHKA 2003 and SWOT analysis.The Data that is examined is the attraction of tourism objects, accessibility, environmental conditions, accommodation, supporting facilities and infrastructure, availability of clean water and safety.Then formulate the internal and external factors of the SWOT matrix as a SWOT analysis. Based on the results of the research of Gunung Pinang nature Tourism has a percentage of ODTWA assessment of 81.63%, so it is worth to be developed, then based on the SWOT analysis that has been done then it is known that the total score of EFI = 1.22 and the total value of EFE = 0.95 score appears that the chosen strategy is in the Quadrant I (one), which is an aggressive strategy. This position that was absolutely strategic ecotourism the further investigated in the the ecotourism program. This is clearly for the purpose of compelling more visitors to Gunung Pinang Natural Tourism.